Insight into the investigation of diamond (C) and Silica (SiO2) nanoparticles suspended in water-based hybrid nanofluid with in solar collector - Bhatti, M. M.; Öztop, Hakan Fehmi; Ellahi, R.; Sarris, Ioannis E.; Doranehgard, M. H. (Elsevier, 2022)
Solar energy conversion systems have encountered numerous issues in recent years due to their poor thermal and optical performance. The fundamental reason for this is that the optical coating of the solar collector is inefficient, and the heat transfer fluid has poor thermal conductivity. As a result, improving the optical thermal performance of energy conversion systems is essential. Therefore in the present article, we discuss in detail about the behavior of diamond (C) and Silica (SiO2) nanoparticles suspended in the water-based hybrid nanofluid floating over an exponentially elastic surface. We have considered the permeable medium to analyze the flow characteristics. Water is incompressible and electrically conductive under the influence of an externally imposed magnetic field. In addition, the viscous dissipation function is taken into account in the energy equation. To carry out the mathematical formulation, an appropriate similarity transformation is used, and the governing equations are transmogrified into nonlinear differential equations. These nonlinear differential equations have been numerically solved using the Successive Linearization method, and the graphical results were presented in relation to the velocity profile, skin friction coefficient, temperature profile, and Nusselt number. A numerical comparison with previously reported results is addressed to analyze the validity of the results and convergence of the proposed methodology. In addition, a comparison is presented between current findings acquired by using the Successive Linearization method and those acquired by using the bvp4c (Matlab built-in command). (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Water-based hybrid nanofluid; Dimaond and Silica nanoparticles; Permeable medium; Solar collector; Successive linearization method (SLM)